Auslander Reiten Quiver of Nakayama Algebra type Dynkin Graph An - Anwar, Faisal; Irawati, I.; Muchtadi-Alamsyah, Intan (Journal of Mathematical and Fundamental Sciences, 2013)
In this paper we will determine Auslander Reiten quiver of Nakayama algebra with quiver type Dynkin graph An for all natural number n â‰¥ 2. The AR-quiver is a visualization of module category of finite dimensional algebras. From the AR-quiver of an algebra A we may know all the isomorphism classes of indecomposable modules in mod A and the homomorphism between them. Once we get the general shape of the AR-quiver of this algebra, we will use it to compute a tilting module of this algebra.